Removal of 17 Cytokines, HMGB1, and Albumin by Continuous Hemofiltration Using a Cellulose Triacetate Membrane: An Ex Vivo Study - Yasuda, Norihisa; Goto, Koji; Yamamoto, Shunsuke; Hidaka, Seigo; Hagiwara, Satoshi; Noguchi, Takayuki (The Journal of surgical research, 2012)
Hemofiltration is often used to treat critically ill patients with renal failure and septic shock. Although hemofiltration has been reported to remove humoral mediators such as cytokines, most studies have investigated the removal of only limited kinds of cytokines. Here, we assessed the removal of 17 cytokines, HMGB1, and albumin by continuous hemofiltration (CHF) with a cellulose triacetate membrane (2.1 m2 or 1.1 m2). The subjects were six healthy volunteers. We collected 400 mL blood into containers with heparin. After adding 1 mg/mL lipopolysaccharide, the blood was incubated at 39°C for 12 h and then filtered through a closed hemofiltration circuit (1 or 2 L/h). Sixty and 240 min after beginning hemofiltration, samples were collected from the outlet (arterial) side, inlet (venous) side, and filtrate port. Blood levels of cytokines, HMGB1, and albumin were determined at each time point. Increasing the flow rate significantly increased cytokine clearance. Increasing the membrane area of the hemofilter significantly changed the sieving coefficient of only five cytokines (IL-1β, IL-6, MCP-1, MIP-1β, HMGB1). For many cytokines, the sieving coefficient did not decline during the 240-min CHF procedure. Although all 17 cytokines, HMGB1, and albumin were detected in the filtrate, the SC and clearance varied widely. For numerous cytokines, clearance increased with the higher filtration flow rate. We demonstrated that CHF removed many cytokines and HMGB1, but was inefficient at removing albumin.